Prostate-Specific Membrane Antigen-Targeted Site-Directed Antibody-Conjugated Apoferritin Nanovehicle Favorably Influences In Vivo Side Effects of Doxorubicin - Dostalova, Simona; Polanska, Hana; Svobodova, Marketa; Balvan, Jan; Krystofova, Olga; Haddad, Yazan; Krizkova, Sona; Masarik, Michal; Eckschlager, Tomas; Stiborova, Marie; Heger, Zbynek; Adam, Vojtech (Scientific reports, 2018)
Herein, we describe the in vivo effects of doxorubicin (DOX) encapsulated in ubiquitous protein apoferritin (APO) and its efficiency and safety in anti-tumor treatment. APODOX is both passively (through Enhanced Permeability and Retention effect) and actively targeted to tumors through prostate-specific membrane antigen (PSMA) via mouse antibodies conjugated to the surface of horse spleen APO. To achieve site-directed conjugation of the antibodies, a HWRGWVC heptapeptide linker was used. The prostate cancer-targeted and non-targeted nanocarriers were tested using subcutaneously implanted LNCaP cells in athymic mice models, and compared to free DOX. Prostate cancer-targeted APODOX retained the high potency of DOX in attenuation of tumors (with 55% decrease in tumor volume after 3 weeks of treatment). DOX and non-targeted APODOX treatment caused damage to liver, kidney and heart tissues. In contrast, no elevation in liver or kidney enzymes and negligible changes were revealed by histological assessment in prostate cancer-targeted APODOX-treated mice. Overall, we show that the APO nanocarrier provides an easy encapsulation protocol, reliable targeting, high therapeutic efficiency and very low off-target toxicity, and is thus a promising delivery system for translation into clinical use.
Keywords: Liver; Nanoconjugates; antigeny povrchové; Animals; apoferritiny; glutamátkarboxypeptidasa II; Doxorubicin; Heart; Kidney; játra; Cell Line, Tumor; výsledek terapie; Mice, Nude; Heterografts; srdce; lidé; Mice; Treatment Outcome; nádory prostaty; Mice, Inbred BALB C; myši; Prostatic Neoplasms; xenogenní modely - testy protinádorové aktivity; imunokonjugáty; nanokonjugáty; Male; myši inbrední BALB C; doxorubicin; Glutamate Carboxypeptidase II; Apoferritins; Xenograft Model Antitumor Assays; zvířata; mužské pohlaví; Antigens, Surface; Immunoconjugates; ledviny; heterografty; myši nahé; nádorové buněčné linie; Humans